(untitled) (Journal of actual problems of jurisprudence, 2022)
The protection of the rights and legitimate interests of victims of criminal offenses and victims of crimes is considered as one of the priority areas for observing law and order in the Republic of Kazakhstan. Part 2 of Article 13 of the Constitution of the Republic of Kazakhstan states: "Everyone has the right to judicial protection of his rights and freedoms." In this regard, the relevance of ensuring the rights of a person who has received moral, material or physical harm from a crime is very high. As stated in Part 3 of Article 12 of the Code of Criminal Procedure of the Republic of Kazakhstan, "The State provides everyone with access to justice and compensation for damage caused in cases and procedure established by law." In this regard, it is known that victimology develops scientific provisions and practical recommendations for the protection of the rights and interests of victims of crimes. To develop scientific provisions and practical recommendations, it is necessary to study the state of crime, the amount of harm caused to crime, or the level of victimization of the population to determine the assessment of crime. In this aspect, it is very important to develop measures to organize victimological prevention, identify shortcomings in prevention measures, and increase the effectiveness of preventive measures. Keywords: victimization; criminalization; crime, latency, victim, injured, criminological case.